The Challenge of Behavioral Bias in Investment Decisions of PT Mirae Asset Sekuritas Users in Malang City - Kurniawan, Mochamad Riski Fajar; Retnasih, Nora Ria (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2025)
Cognitive biases such as loss aversion and herding bias often influence investment decision-making, particularly among retail investors amidst macroeconomic uncertainty due to heated geopolitics, leading to Fear of Missing Out (FOMO) events, which reinforce these behavioral biases when making investment decisions. This study aims to investigate how loss aversion and herding bias influence investment decisions through FOMO, which serves as an intervening variable among investors using the services of PT Mirae Asset Sekuritas in Malang City, with a population of 8,634 investors. The researchers employed an exploratory quantitative design, using a survey method to collect data via an online questionnaire distributed to 100 respondents selected through purposive sampling. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that the direct influence of loss aversion and herding bias has a positive but insignificant effect on investment decisions. Conversely, loss aversion and herding bias have a positive and significant direct influence on FOMO. However, FOMO does not significantly influence investment decisions and is unable to mediate the indirect relationship between loss aversion and herding bias and investment decisions. These findings indicate that although investors experience psychological pressure in the form of FOMO due to behavioral bias, their investment decisions are ultimately based more on rational considerations and self-analysis, supported by financial literacy and access to education from brokers. These results highlight the importance of strengthening financial literacy based on behavioral finance and the need to monitor investment content on digital platforms to mitigate the impact of psychological bias. Keywords: Loss Aversion, Herding Bias, Fear of Missing Out (FOMO), Investment Decisions, Behavioral Finance. Abstrak Bias kognitif seperti loss aversion dan herding bias sering memengaruhi pengambilan keputusan investasi, khususnya di kalangan investor ritel di tengah ketidakpastian makroekonomi akibat geopolitik yang memanas, yang menyebabkan peristiwa Fear of Missing Out (FOMO) memperkuat bias perilaku tersebut ketika mengambil keputusan investasi. Studi ini bertujuan untuk menyelidiki bagaimana loss aversion dan herding bias memengaruhi keputusan investasi melalui FOMO, yang berfungsi sebagai variabel intervening di antara investor yang menggunakan jasa PT Mirae Asset Sekuritas di Kota Malang, dengan populasi 8.634 investor. Peneliti menggunakan desain penelitian kuantitatif eksploratif dengan metode survei untuk mengumpulkan data melalui kuesioner online yang didistribusikan kepada 100 responden yang dipilih menggunakan teknik purposive sampling. Analisis data dilakukan menggunakan metode Partial Least Squares-Structural Equation Modeling (PLS-SEM). Hasil pengaruh loss aversion dan herding bias menunjukkan pengaruh positif tetapi tidak signifikan terhadap keputusan investasi. Sebaliknya, loss aversion dan herding bias memiliki pengaruh langsung yang positif dan signifikan terhadap FOMO. Namun, FOMO tidak secara signifikan memengaruhi keputusan investasi dan tidak mampu memediasi hubungan tidak langsung antara loss aversion dan herding bias dengan keputusan investasi. Temuan ini menunjukkan bahwa meskipun investor mengalami tekanan psikologis dalam bentuk FOMO karena bias perilaku, keputusan investasi mereka pada akhirnya lebih didasarkan pada pertimbangan rasional dan analisis pribadi, yang didukung oleh literasi keuangan dan akses terhadap pendidikan dari pialang. Selain itu penting memperkuat literasi keuangan berdasarkan keuangan perilaku dan perlunya memantau konten investasi di platform digital untuk mengurangi dampak bias psikologis. Kata kunci: Loss Aversion, Herding Bias, Fear of Missing Out (FOMO), Keputusan Investasi, Behavioral Finance.